The Government's Role as a Policy Holder in Encouraging Social Entrepreneurship in Madura Tourism Business - Haryono, Arfin; Rachmadana, Satria Lintang; Wardoyo, Wisnu (Universitas Pendidikan Muhammadiyah Sorong, 2023)
The gap in social action practices between entrepreneurs or companies with the direction and goals set by the government when engaging the private sector to be involved in implementing sustainable social change needs to be evaluated. The principles and philosophy of social entrepreneurship seem to fill this gap by emphasizing and strengthening the entrepreneurial vision so that it is in line with the government's vision. This study aims to examine the roles played by the government in encouraging social entrepreneurship so that it can provide input on current policy weaknesses.